Characteristics of Pickering Emulsion Stabilized by Tea Polyphenols-Starch Nanoparticles - WANG Ran (Shipin Kexue, 2023)
Novel nanoparticles were prepared by addition of tea polyphenols (TP) into gelatinizing waxy maize starch slurry followed by ethanol precipitation and were used to stabilize food-grade Pickering emulsions. The effects of adding TP on the structure and granular properties of starch nanoparticles (SNP) and on the physical stability and oxidative stability of Pickering emulsions were investigated. The results showed that TP could interact with the hydroxyl groups of starch through hydrogen bonding. Moreover, the addition of TP increased the mean particle size of SNP from 187.00 to 233.80 nm, the contact angle from 53.41° to 80.60°, and the absolute value of zeta potential from |−17.20| to |−22.10| mV. Large amounts of small oil droplets were formed in the emulsion stabilized by TP-SNP. Confocal laser scanning microscopy (CLSM) showed that TP-SNP could adsorb onto the oil/water interface to form a physical barrier, which could inhibit oil droplet coalescence. Based on the amount of lipid oxidation products in Pickering emulsions stored for up to 15 days, TP-SNP could delay lipid oxidation of emulsions. These facts indicated that the TP-SNP can be a novel food-grade particle emulsifier with antioxidant capacity for stabilizing Pickering emulsions.